Cataract : an unusual paediatric complication of diabetes mellitus - Daud, Aamir; Nagi, Abdul Ghaffar; Ahmed, Jamil (Maternity and Child Welfare Association of Pakistan, 1998)
Ocular complications of insulin dependent diabetes mellitus (IDDM) are extremely rare in paediatric age group. Transient cataracts have been reported in adolescents with IDDM only in association with severe ketoacidosis and have shown marked improvement after achieving a good metabolic control.We report a case of a 12 year old diabetic girl who presented with bilateral mature cataract formation. Her hyperglycemia was adequately controlled but she was still having the cataracts at three month follow up. Finally, the cataracts were removed surgically and her vision was fully restored.